Higher red cell distribution width and poorer hospitalization‐related outcomes in elderly patients. Issue 8 (4th May 2022) - Kim, Kyoung Min; Nerlekar, Ridhima; Tranah, Gregory J.; Browner, Warren S.; Cummings, Steven R.
Abstract: Background: Red cell distribution width (RDW), an index for variation of red blood cell (RBC) size, has been proposed as a potential marker for poorer outcomes in several aging‐related diseases and conditions. We tested whether greater variability of RBC size, presented as a higher RDW value, predicts poor prognoses among hospitalized patients over 60 years old. Methods: We retrospectively collected data from older hospitalized patients aged ≥60 years between January 2013 to December 2017 at Sutter Health, a large integrated health system in Northern California. The RDW was measured during hospital admission and categorized with 1% intervals (≤13.9, 14.0–14.9, 15.0–15.9, 16.0–16.9, 17.0–17.9 and ≥18.0%). The primary outcome was the rate of in‐hospital mortality and secondary outcomes included 30‐day re‐admission rate and length of hospital stay (in days). Results: A total of 167, 292 admissions from 94, 617 patients were included. The overall in‐hospital mortality rate was 6.3%. As the RDW value increased, the rate of in‐hospital mortality gradually increased from 2.7% for the lowest RDW category to 12.2% in the highest category ( p ‐trend <0.001). The overall 30‐day re‐admission rate after discharge was 12.5% and the rate of 30‐day re‐admission also increased with increasing RDW categories (7.4% in the lowest group vs. 15.8% in the highest group, p ‐trend <0.001). Patients with the highest RDW values at admission stayed 1.5–2.0 times longer in the hospital than patients with lower RDW values who were admitted for the same causes. Conclusions: Greater variability of RBC size is significantly associated with worse prognosis in hospitalized elderly patients, indicating higher mortality, greater risk of early re‐admission, and longer hospital stay days. Risk stratification strategies for hospitalized elderly should include RDW value.